A moving target defence approach for detecting deception attacks on cyber-physical systems. (May 2022) - Babadi, Narges; Doustmohammadi, Ali
Abstract: Cyber-physical systems have posed new challenges, affecting their users. The information security of these systems against cyber-attacks is considered one of the most complex issues in a wide range of defences. The present study proposes a new approach for detecting deception attacks based on moving target defence (MTD). The existing MTD algorithms can only recognize few attacks, including integrity attacks on the cyber-physical system, by limiting the adversary's knowledge of the original system. However, the proposed approach detects replay attacks as well. Moreover, a robust defence system is developed to mislead the adversary and make the attack identifiable from the defender's perspective by introducing a chaotic, hybrid, and extended MTD. Thus, three primary deception attacks, including False Data Injection (FDI), covert, and replay attacks, are detectable based on the proposed approach. The effectiveness of the proposed approach is validated by comparing it with continuous watermarking defence in a cyber-physical testbed.